2000
DOI: 10.1097/00006676-200008000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Complications in Acute Pancreatitis Assessed by Color Duplex Ultrasonography

Abstract: We determined the sensitivity of computed tomography and color duplex ultrasonography in the detection and characterization of vascular complications in acute pancreatitis. The relationship of these complications with the etiology and activity of the disease was assessed. In a prospective study, 189 patients with acute pancreatitis seen in the Department of Gastroenterology. Charité Hospital in Berlin over a period of 38 months underwent color duplex ultrasonography every second day for 3 weeks and thereafter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
112
4
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(129 citation statements)
references
References 16 publications
4
112
4
9
Order By: Relevance
“…49,50 Transient PVT has been reported in 23% of patients with acute pancreatitis and 57% in those with pancreatic necrosis. 51 PVT may also occur with Budd-Chiari syndrome mainly due to stagnant portal venous flow and an underlying prothrombotic state. 52 Recently thrombosis of the portal and mesenteric veins has been described presenting as a medical emergency in troops posted at high altitudes in India.…”
Section: Vascular Endothelial Injurymentioning
confidence: 99%
“…49,50 Transient PVT has been reported in 23% of patients with acute pancreatitis and 57% in those with pancreatic necrosis. 51 PVT may also occur with Budd-Chiari syndrome mainly due to stagnant portal venous flow and an underlying prothrombotic state. 52 Recently thrombosis of the portal and mesenteric veins has been described presenting as a medical emergency in troops posted at high altitudes in India.…”
Section: Vascular Endothelial Injurymentioning
confidence: 99%
“…The reported incidence of SVT in previous studies ranged from 1.8-36.5% [6][7][8][9][17][18][19]. In our cohort of 96 patients, SVT was found in 26 (27.1%) patients.…”
Section: Discussionmentioning
confidence: 43%
“…Though the need for percutaneous catheter drainage was more common in patients with SVT compared to those without SVT, the difference did not reach the statistical significance. Earlier studies have reported that patients with SVT have longer hospital stays compared to those without [6][7][8][9][17][18][19]. Mortality as a direct consequence of SVT has not been reported in patients with AP, although SVT has a high mortality outside the setting of AP [21,22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pancreatitis may induce a spectrum of venous and arterial vascular complications (1)(2)(3)(4). For instance, venous thrombosis is caused by stasis, spasm, and mass effects from the surrounding inflamed pancreas, as well as by direct damage of the venous wall by liberated enzymes (2,5).…”
Section: Introductionmentioning
confidence: 99%